No Time for Transcription-Rapid Auxin Responses in Plants - Dubey, Shiv Mani; Serre, Nelson B C; Oulehlová, Denisa; Vittal, Pruthvi; Fendrych, Matyáš (Cold Spring Harbor perspectives in biology, 2021)
Auxin regulates the transcription of auxin-responsive genes by the TIR1/AFBs-Aux/IAA-ARF signaling pathway, and in this way facilitates plant growth and development. However, rapid, nontranscriptional responses to auxin that cannot be explained by this pathway have been reported. In this review, we focus on several examples of rapid auxin responses: (1) the triggering of changes in plasma membrane potential in various plant species and tissues, (2) inhibition of root growth, which also correlates with membrane potential changes, cytosolic Ca2+ spikes, and a rise of apoplastic pH, (3) the influence on endomembrane trafficking of PIN proteins and other membrane cargoes, and (4) activation of ROPs (Rho of plants) and their downstream effectors such as the cytoskeleton or vesicle trafficking. In most cases, the signaling pathway triggering the response is poorly understood. A role for the TIR1/AFBs in rapid root growth regulation is emerging, as well as the involvement of transmembrane kinases (TMKs) in the activation of ROPs. We discuss similarities and differences among these rapid responses and focus on their physiological significance, which remains an enigma in most cases.
Keywords: vápník; endocytóza; proteiny vázající GTP; rostliny; kořeny rostlin; membránové potenciály; GTP-Binding Proteins; Membrane Potentials; Plant Roots; Plants; Receptors, Cell Surface; Calcium; kyseliny indoloctové; Endocytosis; Indoleacetic Acids; receptory buněčného povrchu; Plant Proteins; rostlinné proteiny